2013
DOI: 10.7860/jcdr/2013/6287.3724
|View full text |Cite
|
Sign up to set email alerts
|

The Volume of the Caudal Space and Sacral Canal in Human Sacrum

Abstract: Introduction: Caudal block is now-a -days a commonly used procedure for pain management and regional anaesthesia. The optimum volume of drugs required to reach the appropriate level is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…An early anatomical study, which was conducted by Lanier and Trotter [60], suggested that the volume of sacral canal in a European population using rising of fluid in the vertebral column was slightly more than 30 mL (range from 12 to 65 mL). In a recent study, the mean recorded volume of the sacral canal in an Indian population sample was 38.26 mL (range from 23.67 to 62.78 mL) [6].…”
Section: Variations In the Morphology Of The Sacral Canal -Complete Dmentioning
confidence: 94%
See 1 more Smart Citation
“…An early anatomical study, which was conducted by Lanier and Trotter [60], suggested that the volume of sacral canal in a European population using rising of fluid in the vertebral column was slightly more than 30 mL (range from 12 to 65 mL). In a recent study, the mean recorded volume of the sacral canal in an Indian population sample was 38.26 mL (range from 23.67 to 62.78 mL) [6].…”
Section: Variations In the Morphology Of The Sacral Canal -Complete Dmentioning
confidence: 94%
“…The diameter of the sacral canal is less than 2 mm in 1% of sacral bones, thus inhibiting the use of 22 G needles [100]. In addition, the available caudal epidural space volume must be estimated preoperatively, so that high block complications are avoided [6]. Ultrasound is a safe, non-invasive and simple method of examination of the exact sacral anatomy, identification of sacral variations and accurate estimation of the volume of epidural space [1].…”
Section: Clinical Significance In Anaesthesiologymentioning
confidence: 99%
“…In both sexes combined, the mean volume of the entire vertebral canal is 38.3 cm 3 and the mean volume of the caudal space is 14.3 cm 3 according to Asghar and Naaz (2013). Both these mean values were significantly larger in males than females.…”
Section: Discussionmentioning
confidence: 98%
“…It has a pyramidal shape and consists of five embryonic fused vertebrae. The coccyx consists of three to five rudimentary vertebrae and is triangular, with its base attached to the sacrum (Asghar & Naaz, 2013). The sacrum has a dorsal convexity but is highly variable in size and shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation